Preparation and investigation of structural and magnetic properties of cadmium-zinc compound (Cd0.3Zn0.7Fe2O4) - Wissam Adel Hussiena; Firas A’aid Najimb (Al-Qadisiyah Journal of Pure Science, 2019)
CdFe2O4 and ZnFe2O4 were prepared by Co-Precipitation method most frequently applied to prepare simultaneous precipitation of more than one component. Co-Precipitation used for achieving high homogeneity to the powder particles. Samples were investigated have phase cubic spinel structure according to the formula (CdxZn1-xFe2O4). Spinel ferrite of the form (Cd0.3 Zn0.7Fe2O4) has been prepared were sintered at room.The research studied structural, morphological and magnetic properties by X-ray diffractometer (XRD). (FE-SEM) field emission scanning electron microscope and (VSM) vibrating sample magnetometer.  The element composition of cadmium-zinc ferrite shows increasing in lattice parameter (8.485887647) were calculated from XRD and crystalline size were determined. The results indicate increasing in volume of crystalline and distance between crystalline surfaces. The (FE-SEM) was used to determine the morphological variations and it’s showed increasing in particle size (47.14 to 210 nm) with the increase of the ferrite concentration. The magnetic properties were measured using the Vibrating Sample Magnetometer showed a narrow hysteresis loop. This indicates that these materials lead to soft-ferrite and that the narrowing of the hysteresis loop shows the loss of magnetism.